Reintroduction failure after negative food challenges in adults is common and mainly due to atypical symptoms. Issue 4 (10th February 2020) - Versluis, Astrid; Knulst, André C.; van Erp, Francine C.; Blankestijn, Mark A.; Meijer, Yolanda; Le, Thuy‐My; van Os‐Medendorp, Harmieke
Abstract: Background: Reintroduction of a food after negative food challenge (FC) faces many obstacles. There are no studies available about this subject in adults. Objective: To investigate the frequency, reasons and risk factors of reintroduction failure in adults. Methods: In this prospective study, adult patients received standardized follow‐up care after negative FCs including a reintroduction scheme and supportive telephone consultations. Data were collected by telephone interview (2 weeks after FC) and questionnaires (at baseline and 6 months after FC(s)): food habits questionnaire, State‐Trait Anxiety Inventory, Food Allergy Quality of Life Questionnaire‐Adult Form and Food Allergy Independent Measure. Frequency and reasons of reintroduction failure were analysed using descriptive statistics and risk factors with univariate analyses. Results: Eighty patients were included with, in total, 113 negative FCs. Reintroduction failed on short‐term (2 weeks after FC) in 20% (95% CI: 13%‐28%). Common reasons were symptoms upon ingestion during the reintroduction scheme (50%) and no need to eat the food (23%). On the long‐term (5‐12 months after FC(s)), reintroduction failure increased to 40% (95% CI: 28%‐53%). Common reasons were atypical symptoms after eating the food (59%) and fear for an allergic reaction (24%). Five risk factors for long‐term reintroduction failure were found: if culprit food was not one of the 13 EU regulated allergens, reintroduction failure at short‐term, atypical symptoms during FC, a lower quality of life and a higher state anxiety. Conclusions and clinical relevance: Reintroduction failure after negative FCs in adults is common, increases over time, and is primarily due to atypical symptoms. This stresses the need for more patient‐tailored care before and after negative food challenges.